Asset management : transforming asset dependent businesses - Lloyd, Chris, 1959-; Corcoran, Michael (ICE, 2019)
"With contributions from leading advisers, industry experts and academic researchers, Asset Management, Second edition is an essential reference on the practicalities of adopting asset management principles, methods and techniques. The book demonstrates how Asset Management can transform the prospects of infrastructure and asset dependent businesses, by reducing risks and costs, and generating increased value for shareholders and stakeholders. Fully updated, this second edition contains a collection of short, authoritative and multi-disciplinary contributions which together provide an accessible and comprehensive overview of asset management best practice that is applicable to all sectors. Individual chapters examine the achievements and future potential of Asset Management, including opportunities posed by digitalisation, climate change and smart cities. This collection will challenge asset management professionals to engage more effectively with business leaders and academia. Asset Management, Second edition is a key reference for practitioners and decision makers working in infrastructure and asset dependent businesses, and will also appeal to students and practitioners new to this area."--Publisher's website